The The mplementation of English Speaking Activities on Students At Modern Al-Furqon Islamic Boarding School, Panaragan Jaya, Tulang Bawang Barat: Speaking activities - Firda Maharani Aneski (Journal of English Development, 2022)
THE IMPLEMENTATION OF ENGLISH SPEAKING ACTIVITIES ON STUDENTS AT MODERN AL-FURQON ISLAMIC BOARDING SCHOOL, PANARAGAN JAYA, TULANG BAWANG BARAT Firda Maharani AneskiUniversitas Islam Negeri Raden Intan Lampung, Indonesia Abstract : Speaking is one of the skill used in communication. This skill can be developed through various activities related to producing oral language. Islamic boarding school is one the institution which allow priority in speaking activities that support the speaking skill.This study focused on the implementation of speaking activities at Modern Al Furqon Islamic Boarding School. The objective of this research was to find out and describe the implementation of speaking activities and enhancement students in English. This is descriptive qualitative research. The intermediate class selected to determine the sample that consisted of 15 students. In collecting the data, the researcher used field notes, interview, documentation and questionnaire. The researcher used three major phases of data analysis: they were data condensation, data display, and drawing and verifying conclusions. From data analysis, the researcher describes the implementation of speaking activities and based on the routines speaking activities made the students increasing speaking skill. Keywords: Implementation, Islamic boarding school, Speaking activities.